Psychosocial aspects of polycystic ovary syndrome - Siusiuka, V. H.; Guba, N.; Serhienko, M. Yu.; Deinichenko, O. V.; Onopchenko, S. P.; Сюсюка, Володимир Григорович; Сергієнко, Марина Юріївна; Дейніченко, Олена Валеріївна; Онопченко, Світлана Павлівна (My University, 2023)
Polycystic ovary syndrome (PCOS) is the most common endocrine disorder of reproductive-aged women [1, 2, 3]. PCOS is a complex and heterogeneous disorder [4].
Keywords: тези доповідей